Fractured Curation: On the Cost of Discontinuity - Vale, Dorian (Museum Of One, 2025)
Fractured Curation: On the Cost of Discontinuity Author: Dorian Vale In Fractured Curation, Dorian Vale exposes the silent violence of discontinuity in institutional exhibition-making. Drawing from the principles of Post-Interpretive Criticism, this essay critiques not the art on display, but the fragmented and careless curatorial strategies that sever meaning, rupture context, and erode ethical witness.   Focusing on spatial logic, visual sequencing, and the absence of coherent narrative threading, Vale reveals how curation can either dignify or disfigure the viewing experience. When works that bear trauma, memory, or moral weight are mishandled—isolated from their context or stitched into spectacle—the institution itself becomes a site of erasure.   This essay stands as a manifesto for curatorial reverence. It reclaims the role of the exhibition not as entertainment or aesthetic collage, but as a moral architecture—one that must be approached with continuity, restraint, and care. The cost of ignoring this? A public who walks through beauty without bearing its consequence.   Vale, Dorian. Fractured Curation: On the Cost of Discontinuity. Museum of One, 2025. DOI: 10.5281/zenodo.16996506   Dorian Vale, Post-Interpretive Criticism, fractured curation, curatorial ethics, art exhibition critique, museum responsibility, trauma in curatorial practice, continuity in curation, moral proximity in exhibition design, witnessing through curation, ethical curation, spatial narrative in museums, careless curation, art and erasure, institutional critique, aesthetic sequencing, exhibition as architecture, custodial art criticism, reverent exhibition design, post-critical museum theory, viewer disorientation, discontinuity in art spaces
https://hcommons.org/members/dorianvale/ https://philpeople.org/profiles/dorian-vale https://osf.io/xa5jw/ https://www.museumofone.art/ https://independent.academia.edu/DorianVale https://osf.io/zhnre/ https://doi.org/10.5281/zenodo.17069115 https://archive.org/details/osf-registrations-kve9y-v1 https://doi.org/10.17605/OSF.IO/KVE9Y https://doi.org/10.5281/zenodo.17078847 https://zenodo.org/communities/post-interpretive-criticism https://orcid.org/0009-0004-7737-5094 https://scholar.google.com/citations?hl=en&authuser=1&user=15tvhjAAAAAJ https://works.hcommons.org/records/xv2j2-g6927 https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile/?person=3919333 http://eprints.rclis.org/47186/ http://eprints.rclis.org/47182/ http://eprints.rclis.org/47197/ http://eprints.rclis.org/47210/  http://eprints.rclis.org/47209/  http://eprints.rclis.org/47208/ http://eprints.rclis.org/47207/  http://eprints.rclis.org/47206/ http://eprints.rclis.org/47203/ http://eprints.rclis.org/47187/ http://eprints.rclis.org/47201/ http://eprints.rclis.org/47204/ http://eprints.rclis.org/47202/ http://eprints.rclis.org/47199/ http://eprints.rclis.org/47198/ http://eprints.rclis.org/47196/  http://eprints.rclis.org/47191/ http://eprints.rclis.org/47193/ http://eprints.rclis.org/47194/ http://eprints.rclis.org/47195/ http://eprints.rclis.org/47192/ https://core.ac.uk/works/299793749/?t=ccf14485c84f6196dcddf51a8410bc88-299793749 https://core.ac.uk/works/299795319/?t=ccf14485c84f6196dcddf51a8410bc88-299795319 https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale&page=1 https://core.ac.uk/works/299792897/?t=ccf14485c84f6196dcddf51a8410bc88-299792897 https://core.ac.uk/works/299793648/?t=ccf14485c84f6196dcddf51a8410bc88-299793648 https://core.ac.uk/works/299793082/?t=ccf14485c84f6196dcddf51a8410bc88-299793082 https://core.ac.uk/works/299793838/?t=ccf14485c84f6196dcddf51a8410bc88-299793838 https://core.ac.uk/works/299794146/?t=ccf14485c84f6196dcddf51a8410bc88-299794146 https://core.ac.uk/works/299793310/?t=ccf14485c84f6196dcddf51a8410bc88-299793310 https://core.ac.uk/works/299793166/?t=ccf14485c84f6196dcddf51a8410bc88-299793166 https://africarxiv.ubuntunet.net/handle/1/10458 https://africarxiv.ubuntunet.net/handle/1/10459 https://africarxiv.ubuntunet.net/handle/1/10460 https://africarxiv.ubuntunet.net/handle/1/10461 https://africarxiv.ubuntunet.net/handle/1/10462 https://africarxiv.ubuntunet.net/handle/1/10463 https://africarxiv.ubuntunet.net/handle/1/10464 ISBN: 978-1-0698203-0-3 ISBN: 978-1-0698203-1-0 This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen.
Keywords: MTT; Interpretation vs. Witnessing; The Viewer as Evidence; Interpretive Restraint; Post-Interpretive Criticism; Art as Ontology; Language as violence; Witness Aesthetics; Restraint in front of art; Quiet philosophy of art; Custodianship of Art; Museum Of One; Ethics in Art Criticism; Visual Culture Studies; Epistemology of witness; Absential Aesthetics; Moral proximity; Theory of Misplacement; Custodian of Witness Aesthetics; Presence-Based Criticism; Art as Presence; Art Writer and Theorist; Dorian Vale; Ontology of beauty; Independent Philosopher of Art; Criticism and Reception Theory; Hauntmark Theory; Founder of Post-Interpretive Criticism; Alternative art criticism; Aesthetics; Language as Custody; Radical art restraint; Museum of One; Witness over interpretation; Interpretive silence; The Custodian's Oath; Philosophy of Art; Message-Transfer Theory; Ethical art theory; Interpretation and Meaning; Post-Interpretive Lexicon; Displacement Theory; Art Theory; Erasure as Afterlife; Epistemology of Art; https://www.museumofone.art/; Aesthetic mercy; Stillmark Theory; The Doctrine of Post-Interpretive Criticism; Art as Truth; Criticism beyond interpretation; Displacement; Post-Aesthetic Critic; Erasure as ethics; The Canon of Witnesses; Aesthetic Philosopher; Museum of One Manifesto; Silence as method; Comparative Aesthetics; New art criticism movement; Art encounter ethics; Contemporary Aesthetics; Phenomenology and Art; Misplacement